THE STRUGGLE OF SYMBOLIC CAPITAL IN RUSSIAN TOURIST MARKET OF BALI TOURISM - Gede Ginaya; A.A. Ngr. Anom Kumbara; I Nyoman Darma Putra; I Nyoman Sukiada (E-Journal of Cultural Studies, 2020)
A professional tour guide is regarded as a front-liner of the tourism and the ambassador of his/her country. Therefore, the performace of a tour guide is very important as a quality assurance of services in order to fulfill the tourists’ satisfaction. One of the important things to satisfy the tourists is through mastering the language, because if the tour guide speaks the language fluently and accurately, the commucation will be well maintained and all information can be successfully delivered. In this case, mastering Russian language, which is categorized into one of the latest foreign languages in the tourism business of Bali, is deemly needed by the Russian tourists in order to get sufficient information about the culture of the indigenous community. This study aimes at investigating the mastery level of the tour guide’s Russian language related to the struggle of symbolic capital between foreign representatives and local tour guides. By applying a descriptive qualitative research, the data was collected through observation, interview, and document review. The theory used to undertake this study is Bourdieu’s social practice theory which involves capital, habitus, and field. The data that has been classified is analyzed by qualitative descriptive method with an inductive-metodological paradigm which is seting up the discussion from particular principles to the general in order to obtain a conclusion. The result of data analys is presented by formal and informal method. The study reveals that the mastery of Russian language for a professional tour guide has been proven to compete with foreign tour guides in preserving the Balinese culture and empowering local community in tourism participation. Keywords: Russian language, professional tour guide, capital symbolic.